Negative Imperfective Verb Form in Kanuri: A Case Study of Nyariwa Kanuribe - Muhammad Hussaini Bulama; Kalli Hussaini (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This paper examines Negative Imperfect Verb Form in Kanuri text within the framework of descriptive linguistics adopting the works of Cyffer (2009) model of approach in analyzing negation types in Kanuri. In conducting the research, both sources of data collection were employed: the primary source includes a Kanuri written text Nyariwa Kanuribe, where all the various place where the Negations negating the imperfective verb occurred where underlined and extracted from the text for data presentation and analysis. The study also employed the secondary source of data collection where three linguists from the Kanuri section of the department of languages and Linguistics University of Maiduguri, Nigeria were engaged to validate the data collected from the text. The outcome of the study reveals that there are two particle used in negating the imperfective verbs form in the text and study identified these particles are ba and bawo are bound morpheme negating imperfective verbs form in Kanuri. Finally the study identified eighty one instances of the two negation particle with their number of occurrences and their percentages in the text analyzed.